2017
DOI: 10.1111/cei.13011
|View full text |Cite
|
Sign up to set email alerts
|

Complement and contact system activation in acute congestive heart failure patients

Abstract: Recent experimental data indicate a pathogenic role of complement activation in congestive heart failure (CHF). The aim of this study was to evaluate contact and complement systems activation in patients hospitalized for an acute episode of CHF. Forty-two of 80 consecutive patients admitted at our hospital with confirmed diagnosis of acute CHF were enrolled. They underwent blood sampling within 24 h from admission (T0) and at clinical stability (T1). Patients were stratified for ejection fraction (EF) based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Similarly, these DEGs were also markedly involved in in ammatory/immune response, response to stress, oxidative stress, and brosis. The exact same terms enriched from DEPs and DEGs furtherly highlighted the key roles of the processes of ECM organization and response to stress, as well as the complement and coagulation cascades signal pathway, in the mechanisms of ICM, which were consistent with previous researches [19][20][21].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, these DEGs were also markedly involved in in ammatory/immune response, response to stress, oxidative stress, and brosis. The exact same terms enriched from DEPs and DEGs furtherly highlighted the key roles of the processes of ECM organization and response to stress, as well as the complement and coagulation cascades signal pathway, in the mechanisms of ICM, which were consistent with previous researches [19][20][21].…”
Section: Discussionsupporting
confidence: 89%
“…Suffritti et al. also observed in the patients with heart failure that the levels of C4 and C5b9 did not draw back when their cardiac situation became stable; and the C3 levels even manifested confusing elevation at this point . More than C3, de Haan et al.…”
Section: Discussionmentioning
confidence: 97%
“…Frey et al found that elevated levels of C3c subset, a stable C3-conversion product, even predicted better prognosis in patients with systolic heart failure [22]. Suffritti et al also observed in the patients with heart failure that the levels of C4 and C5b9 did not draw back when their cardiac situation became stable; and the C3 levels even manifested confusing elevation at this point [23]. More than C3, de Haan et al reported that the deficiency of gene encoding C5a receptor failed to significantly improve cardiac fibrosis and collagen degradation in pressure-overload heart failure mice, suggesting the showing that Arg1 (arrow) was the most significantly upregulated gene in BMDMs incubated with CFB.…”
Section: Discussionmentioning
confidence: 99%
“…In stage C dogs, C3, a member of the complement system, was up-regulated, whereas other complement proteins (i.e., C4a, C7, and C8) were down-regulated, indicating a pathophysiological involvement of the complement system. The increases in C3 in human patients with CHF is related to chronic immune-inflammatory activation, leading to adverse left ventricular remodeling and aggravation of heart failure [ 31 , 32 ], and poorer outcome [ 31 , 33 ]. The role of complement proteins, as potent therapeutic and prophylactic targets to slow the progression of CHF, should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%